Being thunder [videorecording (DVD)] (Film Movement, 2021)
"Sherente, a Two Spirit Genderqueer teenager from Rhode Island's Narragansett tribe performs traditional dance in competitions at annual pow wows in New England. There is no formal rule which prohibits Two Spirit Genderqueer people from performing in a category different from their birth gender. Wearing female fancy shawl regalia, Sherente dances with joy and beauty. Behind the scenes tribal leaders manipulate Sherente's scores or disqualify them outright because of their belief in traditional binary gender roles. Blindsided by ongoing dishonesty and deception, Sherente continues to perform in spite of insensitive behavior by tribal leaders and others in their community. Sherente's enduring courage and self-respect are met with an outpouring of support from family, pow wow attendees, and fellow dancers"--Internet Movie Database